Effects of self and familiarity on change detection in patients with schizophrenia. (February 2017) - Kochs, Anna; Köhler, Stephan; Merz, Holger; Sterzer, Philipp
Abstract: In schizophrenia, processing of self-related stimuli has been shown to be altered. It is unclear whether altered self-processing in schizophrenia is confined to cognitive functions such as self-recognition, or whether it pertains to automatic lower-level perceptual processes. Visual face processing was tested in patients with schizophrenia (n=36) and healthy controls (n=33). Using a change detection paradigm (self, famous, unknown faces), we tested whether self-related stimuli gain access to awareness preferentially. The task was unrelated to face category, thus probing implicit processing of the face identity information. Furthermore we explored hemifield differences, the association of preferential self-processing with disease insight and with schizophrenic symptom severity. Change detection was overall enhanced for one's own face and familiar faces compared to unknown faces. There were no group differences regarding perception of self-related or familiar stimuli. The enhancing effect of self and familiarity on change detection was smaller in patients with more severe symptoms. We found no association between implicit visual self-perception and insight in schizophrenia. The privileged access of self-related visual information is not impaired in patients with schizophrenia. The reduced overall left-hemifield advantage for face-change detection points to an altered lateralization of face processing in patients with schizophrenia. Highlights: Intact change-detection of self and familiar faces in schizophrenia patients. Unimpaired low-level processing of face identity in schizophrenia patient. Impaired insight in schizophrenia patients not related to self-processing deficit. Altered hemifield lateralization of face processing in schizophrenia patients.